Effects of Ulinastatin on Liver Warm Ischemia Reperfusion Injury in Mice. (July 2018) - Li, Wei; Li, Peidong; Li, Zhuonan; Liu, Hongyu; Guan, Lianyue; Zhang, LIanbo
Abstract : Objective: Ulinastatin, a trpsin inhibitor, has been reported that can inhibits the liver inflammation and improves the liver function. The role of UTI on liver warm ischemia reperfusion injury (IRI) and the underlying mechanisms remain to be further investigated. Method: In bred C57BL/6 mice and liver warm IRI model were employed. The ligamentum of hepatoduodenale was clamped for 45mins and followed with reperfusion of 1 hour, 6hour, 24hour, respectively. UTI was treated preoperatively. Serum enzyme release, liver cell histology and apoptosis, and Caspase-3 mRNA & Fas mRNA expression from the liver tissues were examined, respectively. Results: ALT/AST levels are remarkably lower in IRI+UTI group than IRI group at reperfusion time of 1hour, 6hour, and 24 hour. Observed under light microscope of 6 hours of reperfusion sample, hepatic cell was significantly edema degeneration, with partial liver cell vacuolization obviously, some patchy necrosis, sinusoidal congestion and become narrow. RT-PCR result shows that expression of Caspase-3mRNA and Fas mRNA are significantly higher in IRI group than that in IRI+UTI group(P<0.05). Compared with SO group, expression of IL-6 and TNF-α of IRI group and UTI group is up-regulated (P<0.05). Compared the latter two group, IRI+UTI group's expression is significantly down regulated. Apotosis of liver cells in IRI+UTI group is relieved in contrast to IRI group(P<0.05), while SO group shows a negative resault. Conclusion: Ulinastatin has the ability to inhibit releasing of inflammatory factors by hepatocytes after hepatic ischemia reperfusion, and helps clean ROX and endotoxins. Meanwhile, down regulate expression of Caspase-3 mRNA and Fas mRNA, in this way reduce hepatocytes apoptosis, as a resault significantly prevent liver ischemia reperfusion injury through multiple links. Nature Science Foundation of China (NSFC) (81170416; 81273264); International cooperation fund of Jilin Science & Technology Committee (2016322).